Profissão: Oficial da Marinha Mercante - Santana, Alexandre Moraes Rocha (2016)
The objective of this research is the work relationships of the Seafarer Officer in Brazil, sheltering both qualifications: Deck Officer and Engineer Officer, a kind of seafarer acting on the cargo operations. Thus, this research aims at understanding the specificities of the Merchant Marine Officialdom profession and the relevance of this activity for the society, for capitalism and for globalization. In relation to the relevance of the activity, the development of navigation and its participation in the cargo shipping around the world were considered, which corresponds to around 80% of all the cargo shipped worldwide, as well as the importance of navigation, referring to cargo shipping throughout history and its participation in capitalism and in globalization. Referring to the specificities of the profession, the militarized influence in the profession was considered, even though it is a civil and commercial activity, which influences the professional formation, organization and job assignment. The professional competences and its relations with immaterial labor were also analyzed, as well as daily work, confined and isolated work, experiences between work time and nonwork time. The research was conducted through semi-structured interviews with ten Seafarers Oficcers, by e-mail, whose questionary is in the introduction of this dissertation, with qualitative approach. The data revealed the peculiarities of the Merchant Marine Officialdom profession, which distinguish it from the others professions